Occurrence of arbuscular mycorrhizal fungi in high altitude sites of the Patagonian Altoandina region in Nahuel Huapi National Park (Argentina) - Velázquez, María Silvana (2016)
Knowledge of the occurrence and diversity of arbuscular mycorrhizal fungi (AMF) in National Parks is essential for the establishment of policies for conservation. The aim of this study was to characterize the AMF communities in the Patagonian Altoandina region in Nahuel Huapi National Park, Argentina. We surveyed AMF spores associated with the rhizospheres of 9 plant species in the Patagonian Steppe (PS), Challhuaco Hill (ChH), Catedral Hill (CH), and Tronador Hill (TH) regions and detected a total of 27 Glomeromycota species. Acaulospora laevis was dominant at all sites. The AMF community was dominated by Acaulosporaceae, as regards the number of species and contribution of each one to the total number of spores. Three Glomeromycota families were detected at PS, the site with the lowest elevation; whereas five to six families were detected at ChH, CH, and TH. Cluster analysis indicated that the AMF communities were grouped according to habitat. We concluded that certain patterns of the AMFcommunity structure detected were equivalent to those of high-altitude environments from other studies, while others were unique to the Patagonian region; thus suggesting that historical influences like dispersion and speciation played a critical role in shaping AMF community composition in such high-altitude environments.